Fatal discord : Erasmus, Luther, and the fight for the western mind - Massing, Michael (Harper, an imprint of HarperCollinsPublishers, 2018)
Presents an intellectual assessment of the rivalry between Desiderius Erasmus and Martin Luther that examines their respective characters and belief systems, sharing insights into their enduring influence and proper historical roles in western tradition.